BENZENE EXPOSURE ANALYSIS IN INFORMAL SHOE INDUSTRY WORKERS IN SUKAJAYA VILLAGE, WEST JAVA VIA LEUKOCYTE COUNT AND S-PHENYLMERCAPTURIC ACID MEASUREMENT IN URINE - Agustina, Lora; Wulandari, Ririn Arminsih (YCAB Publisher & IAKMI SULTRA, 2019)
Background: Benzene is a hematotoxic and carcinogenic compound contained in the glue used in the shoe industry. This compound has been suspected of causing decreased leukocyte counts, which is one of the blood cell production disorders. Benzene exposure can be determined by measuring the concentration of S-phenylmercapturic acid (S-PMA) in urine.Objective: This study was conducted to determine the association between S-PMA urine concentration and the leukocyte count of shoe industry workers.Methods: The study design was cross sectional and the data were collected by conducting interviews, analyzing urine samples for S-PMA concentrations, and conducting blood examinations. Chi square and multiple logistic regression were used for the analysis.Results: The results showed there were no concentrations of S-PMA in urine that exceeded the Biological Exposure Index (BEI) value (â‰¤25 Î¼g/g creatinine). Higher S-PMA concentrations in this study show a higher risk of decreased leukocyte counts. When controlling for age, duration of work, history of infection, Body Mass Index (BMI), smoking, occupation, and exercise, workers with high S-PMA urine concentration were found to be at higher risk of a decreased leukocyte count.Conclusion: Although S-PMA urine concentrations were still below BEI values, workers with higher S-PMA urine concentration were more at risk of leukocyte counts of < 5.0 x 103/Î¼L. The decrease in the minimum BEI S-PMA limit value was lower than the current standard may need to be considered.